Respuesta :

You just need to translate the sentences into formulas: let x be the number, we have

  • The difference of a number and 7 means [tex]x-7[/tex]
  • Twice that difference means [tex]2(x-7)=2x-14[/tex]

So, the left hand side of our equation is 2x-14. Similarly, we have

  • The sum of the number and 9 means [tex]x+9[/tex]
  • Three times that sum means [tex]3(x+9)=3x+27[/tex]

So, the right hand side of our equation is 3x+27. We can set and solve the equation

[tex]2x-14=3x+27 \iff -14-27=3x-2x \iff -41=x[/tex]

So, the solution is -41.

ACCESS MORE